Clinicians' opinions on recommending aspirin to prevent colorectal cancer to Australians aged 50–70 years: a qualitative study. Issue 2 (5th February 2021) - Milton, Shakira; McIntosh, Jennifer; Yogaparan, Thivagar; Alphonse, Pavithran; Saya, Sibel; Karnchanachari, Napin; Nguyen, Peter; Lau, Phyllis; Macrae, Finlay; Emery, Jon
Abstract : Objectives: Australian guidelines recommend all adults aged 50–70 years old without existing contraindications consider taking low-dose aspirin (100–300 mg per day) for at least 2.5 years to reduce their risk of developing colorectal cancer. We aimed to explore clinicians' practices, knowledge, opinions, and barriers and facilitators to the implementation of these new guidelines. Methods: Semistructured interviews were conducted with clinicians to whom the new guidelines may be applicable (Familial Cancer Clinic staff (geneticists, oncologists and genetic counsellors), gastroenterologists, pharmacists and general practitioners (GPs)). The Consolidated Framework for Implementation Research (CFIR) underpinned the development of the interview guide. Coding was inductive and themes were developed through consensus between the authors. Emerging themes were mapped onto the CFIR domains: characteristics of the intervention, outer setting, inner setting, individual characteristics and process. Results: Sixty-four interviews were completed between March and October 2019. Aspirin was viewed as a safe and cheap option for cancer prevention. GPs were considered by all clinicians as the most important health professionals for implementation of the guidelines. Cancer Council Australia, as a trusted organisation, was an important facilitator to guideline adoption. Uncertainty about aspirin dosage and perceived strength of the evidence, precise wording of the recommendation, previous changes to guidelines about aspirin and conflicting findings from trials in older populations were barriers to implementation. Conclusion: Widespread adoption of these new guidelines could be an important strategy to reduce the incidence of bowel cancer, but this will require more active implementation strategies focused on primary care and the wider community. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12620001003965).